2014
DOI: 10.3390/min4020553
|View full text |Cite
|
Sign up to set email alerts
|

Chemoorganotrophic Bioleaching of Olivine for Nickel Recovery

Abstract: Bioleaching of olivine, a natural nickel-containing magnesium-iron-silicate, was conducted by applying chemoorganotrophic bacteria and fungi. The tested fungus, Aspergillus niger, leached substantially more nickel from olivine than the tested bacterium, Paenibacillus mucilaginosus. Aspergillus niger also outperformed two other fungal species: Humicola grisae and Penicillium chrysogenum. Contrary to traditional acid leaching, the microorganisms leached nickel preferentially over magnesium and iron. An average s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 19 publications
(33 reference statements)
0
8
0
2
Order By: Relevance
“…Unfortunately, the impact of ultrasound was examined only on the fungal bioleaching of olivine (i.e., bacterial sonobioleaching was not examined). On sonication, an increase from 9.9% to 15.7% was observed in Ni leaching over 17 days [99]. Other metals present in the ore (such as Mg, Al, Si and Cr) increased marginally.…”
Section: Sonobioleaching With Bacteriamentioning
confidence: 95%
See 1 more Smart Citation
“…Unfortunately, the impact of ultrasound was examined only on the fungal bioleaching of olivine (i.e., bacterial sonobioleaching was not examined). On sonication, an increase from 9.9% to 15.7% was observed in Ni leaching over 17 days [99]. Other metals present in the ore (such as Mg, Al, Si and Cr) increased marginally.…”
Section: Sonobioleaching With Bacteriamentioning
confidence: 95%
“…In sonobioleaching, ultrasound can be applied during the growth of the microorganism and/or leaching (Table 1) [96,99]. When applied during growth, low intensity should be used, since positive effects on bacterial growth have been observed [60,80].…”
Section: Future Directions In Sonobioleachingmentioning
confidence: 99%
“…Another opportunity is the recovery of metallic components (primarily nickel and chromium) from carbonated olivine. Santos et al (2015b) and Chiang et al (2014) have reported on nickel extraction efforts from carbonated olivine using chemical and biological means, respectively. It has been found that at elevated acidity, more nickel can be extracted from carbonated olivine compared to fresh olivine.…”
Section: Product Applicationmentioning
confidence: 99%
“…A preliminary test was performed using a large variety of organic acids: citric acid (HOC(COOH)(CH2COOH)2), oxalic acid (HOOCCOOH), succinic acid (HOOC(CH2)2COOH), lactic acid (CH3CH(OH)COOH), acetic acid (CH3COOH), formic acid (HCOOH) and butyric acid (C3H7COOH). These organic acids were chosen as they are reportedly produced by microorganisms utilized in bioleaching of silicate minerals [21,22]. Based on preliminary experimental results ( Figure S5) the three most promising organic acids, citric acid, formic acid, and lactic acid were selected for further use in the experiments discussed hereon.…”
Section: Leachingmentioning
confidence: 99%